Santos/as de cemitério e protagonismo feminino: estudo de caso de Maria Féa e Menino Onofre na cidade de Santos-SP - Couceiro, Ana Paula Nogueira (2024)
Popular Catholicism has been integral to Brazilian life since the colonial era, emerging from the cultural intermingling of the groups involved in Brazil's colonization: the indigenous peoples with their practices of communication between the living and the dead; the European colonizers with their Catholicism and residual pagan beliefs from Iberian Peninsula; and the enslaved Africans with their traditions of spiritual beliefs. This dissertation examines the devotion to cemetery saints as an expression of popular Catholicism in Santos, a coastal city in São Paulo. As Popular Catholicism lacks religious experts and is organized around popular devotions, the present study addresses a gap in the field of Religious Studies concerning this topic. The research is structured in a literature review, followed by interviews. Twelve women, primarily from lower socioeconomic backgrounds and over the age of 35, were interviewed. They shared their relationships of trust and symbolic exchange with Maria Féa and Menino Onofre, two cemetery saints, highlighting the significant role of female agency in this religious practice. The testimonies revealed that devotees do not merely await the saints' intervention but actively engage in efforts to achieve their goals. Additionally, the study identified the use of the Internet to disseminate devotion to these cemetery saints through articles and videos, including contributions from a devotee, which aids in the spread and perpetuation of their cult